Application of Visual Media Pop-Up Book in English Learning in Elementary School - Rinny Rorimpandey (Journal of English Culture, Language, Literature and Education, 2023)
It is good if English has been introduced since childhood to Indonesian children so that it will not become a frightening specter for them later. In the 2013 curriculum, elementary schools do not have English as a subject, because English has always been a local content subject. However, the obstacle in teaching English is that there are still many elementary school students who are not interested in this subject. The reason is that English is a new language for them and they don't have sufficient vocabulary mastery. Because of that, during English lessons, the teacher teaches only a few students who pay attention, there are many students who play, they feel bored and unenthusiastic when learning English. This was faced by students of the SD GP in Raanan Baru Village, Motoling District, causing them to be unenthusiastic and less creative when it came to English lessons. Therefore, teachers must pay attention to learning models that are appropriate to their goals, not boring but can motivate students and attract their attention, namely choosing learning media can help improve vocabulary mastery. Therefore, in this study, the writer used Visual media pop-up book to improve English vocabulary mastery of the students of SD GP Raanan Baru. The results of this study showed a significant difference, namely the results of the post-test were better than the pre-test as evidenced by the average post-test (T2) score of 71.2 with a standard deviation of 13.5, while the average value of the pre- test (T1) is 30 and the standard deviation is 11.1